PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI SULAWESI TENGGARA - Suharto Suharto (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study was to examine and explain the effect of work discipline, work environment and leadership simultaneously on the performance of the employees of the Investment and One Stop Service Office of Southeast Sulawesi Province (DPMPTSP Prov. Sultra). This research approach is a survey with an explanatory research design. Data collection was carried out in a cross-sectional manner using an instrument in the form of a questionnaire. The population and sample of this study were 56 employees of the Office of Investment and One Stop Services of Southeast Sulawesi Province (DPMPTSP Prov. Sultra). The sampling technique used in this study was purposive sampling, namely sampling based on objectives or criteria. The analytical tool used is Multivariate Regression Analysis.The results showed that work discipline partially had a positive and significant effect on the performance of the employees of the Office of Investment and One Stop Services of Southeast Sulawesi Province (DPMPTSP Prov. Sultra). The work environment partially has a positive and significant effect on the performance of the employees of the Office of Investment and One Stop Services of Southeast Sulawesi Province (DPMPTSP Prov. Sultra). Leadership partially has a positive and significant effect on the performance of the employees of the Office of Investment and One Stop Services of Southeast Sulawesi Province (DPMPTSP Prov. Sultra). Simultaneously work discipline, work environment, and leadership have a positive and significant effect on employee performance at the Investment and One Stop Service Office of Southeast Sulawesi Province (DPMPTSP Prov. Sultra).